PELATIHAN INTERNET DASAR DAN APLIKASI E COMMERCE KELOMPOK TANI AMBUDI MAKMUR BANGKALAN - Nachnul Ansori; Trisita Novianti (Buletin Udayana Mengabdi, 2014)
issue of majority owned by Small and Medium Enterprise (SME) generally is business managerial focused on marketing aspect. In the event of Kelompok Tani Ambudi Makmur II has business unit for salacca zalacca in UD. Budi Jaya. Product selling currently only in center store of hand gift in Bangkalan. Besides, others like transfer of knowledge and technology of community service program is the minimum competency of human resource in operating/managing website. The condition due to low education degree of the owner and management SME that just junior high school. Based on the above condition, proposed community service activity namely IbM (Ipteks Bagi Masyarakat) was conducted in order that transfer knowledge and skill in computer field to SME’s Management by considering the constraint relating to human resource. These program are training of basic computer like Microsoft Word and Excell, internet, managing web e commerce. Basic computer needs to support daily administrative operation management such financial report, working report, invitation so on. Meanwhile, IbM’s Program proposed design web e commerce by web account ; www.ambudimakmur.com as medium of promotion and product marketing for salacca zalacca widely. This program also facilitied the training for the owner and SME’s Management as the administrator web in managing and maintaining e commerce included the on line transaction.Key word: salacca zalacca, SME, IbM, e commerce